Pelatihan Desain Konten Instagram untuk Penguatan Branding SD Qaryah Thayyibah Purwokerto - Purwati, Yuli; Al Fauzan, Lukman; Limaz Morallez, Airlangga (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Tanah Laut (Politala), 2024)
As an educational institution, schools must have strong branding so that parents will see the reputation and value of the school. Currently, SD Qita has several social media, usually used to provide various information related to the school, such as vision and mission, student activities, events and school registration information. The analysis results show that the current Instagram feed display and content design still do not show the branding of SD Qita, so visitors cannot immediately understand the school's image if they only glance at the feed display and Instagram content design. The achievement of this service activity is that the teachers gain knowledge related to creating Instagram content design, creating video reels and knowledge related to Instagram SEO further to strengthen the branding and value of SD Qita.